Education for sustainable development and the professional curriculum. Issue 3 (1st September 2016) - Reid, Colin T.
Abstract : Studies of education for sustainable development have tended to overlook the significance of professional accreditation requirements in determining the curriculum in many disciplines. A study of the accreditation criteria for the many professionally recognised degrees at one university reveals a range of levels of engagement with sustainability issues and of responses to these by teaching staff. The legal professions are mostly among those which pay least attention to issues beyond narrow technical competence.